Cancer Survivors, childhood cancer, chemotherapy, radiotherapy, follow up - Fidela de Fátima Muro-Cieza, Johanny (2024)
Survival rates in children with cancer have increased over the years, however the consequences of the oncological treatment received have an impact on different organs and tissues, thus, holocranial radiotherapy and chemotherapy that penetrates the central nervous system can cause consequences. neurocognitive, long-term ocular complications include cataracts, glaucoma, retinopathy and severe dry eye, the use of platinum-based chemotherapy and radiotherapy is associated with hearing loss. The lungs and lung function are vulnerable to injury from oncological treatment and after hematopoietic stem cell transplantation; The use of anthracyclines constitutes the main cause of cardiomyopathy in survivors. At the gastrointestinal level, alkylating agents and anthracyclines can influence the risk of liver and gastrointestinal mucosal damage, and at the kidney level, chemotherapeutic agents such as ifosfamide, cisplatin and carboplatin. Pelvic/abdominal radiation and high-dose alkylating chemotherapy can cause premature ovarian failure in women and azoospermia in men. Thyroid complications are common in survivors, and those exposed to cranial radiation and those with total body irradiation (TBI) are at risk of experiencing linear growth restrictions and growth hormone deficiency. Finally, in some cases a second neoplasm usually develops. The objective of this review is to know the different sequelae of oncological treatment and standardize the follow-up of the patients involved for their timely detection.